Nursing management for a patient with pulmonary infection and orotracheal intubation (1例肺部感染气管插管患者的护理体会) - LI Na (李娜); SUN Lei (孙磊); ZHOU Jie (周洁) (中西医结合护理)
This paper reviewed the clinical data and treatment of a patient with pulmonary infection-associated fever and coma, and summarized related nursing interventions. The patient received comprehensive therapy including mechanical ventilation, anti-infection and anti-inflammatory treatment, reducing edema and eliminating phlegm. During the anti-infection treatment, targeted nursing intervention against fever, airway management, skin care and enteral nutrition were carried out. (本文回顾1例发热、昏迷伴肺部感染患者的临床治疗措施, 总结相关护理经验。给予患者呼吸机辅助通气, 联合抗感染、抗炎、减轻局部水肿、化痰等综合治疗。抗感染治疗期间, 针对发热实施护理干预, 加强气道管理, 同时给予皮肤护理和肠内营养支持。)